Oral Contraceptive Use and the Risk of Cardiac Events in Long QT syndrome Patients - BPharm, Abeer Abu-Zeitone (2014)
BACKGROUND: In prior clinical studies of patients with long QT syndrome (LQTS), pregnancy was associated with fewer cardiac events (CEs) compared to before or after pregnancy. In recent animal studies involving rabbits with LQTS mutations, progesterone had favorable effects on CEs compared to estrogen. The effect of oral contraceptive therapy with its high progesterone/estrogen ratio on the risk of CEs in LQTS patients has not been examined. OBJECTIVE: To study the effect of oral contraceptive use on the risk of CEs in LQTS patients. METHODS: We studied 174 patients from the Rochester-based LQTS Registry who responded to a questionnaire about their oral contraceptive use. We used time-dependent Cox regression to estimate the hazard ratio for recurrent CEs when patients were taking versus not taking oral contraceptives during nonpregnancy periods. For this recurrent events analysis, the Prentice-Williams-Peterson (PWP) model was used, and the time origin was defined as the onset of menarche. We adjusted for the baseline QTc interval, history of CEs prior to menarche, age at menarche onset, number of births, time-dependent β- blocker therapy and LQTS genotype. RESULTS: No differences in the risk of CEs for the times LQTS patients were using versus not using oral contraceptives was found in the general LQTS population (hazard ratio=1.01, p=0.95) or in analyses of LQTS subsets (p>0.2). CONCLUSIONS: Oral contraceptive therapy use did not affect LQTS-related CEs in the study population. Oral contraceptives did not show beneficial or harmful effects in this patient group.